British Colonialism: The Development of Health Institutions in Perak, 1911-1939 - Sukri, Nur Liyana Mohd (European Publisher, 2019)
This paper discusses the effects of British colonialism on the development of health institutions in Perak beginning before the First World War until after the recession. This study attempts to evaluate the establishment of a health institution during this period on whether it had justified the British fulfillment of the ‘Whiteman’s burden’ mission or leverage its manipulation of hospital and disease control regulation as a tool to maintain its colonial presence. Based on the British Administration Report of Perak, Perak Government Gazette, along with other primary and secondary sources, this study discovered that the development of health institutions and hospitals during the British Imperialism phase is in the process of strengthening their power and economy exploitation in Perak between 1911 and 1939. The British had leveraged health institutions and hospitals as an element of ‘social colonialism’ to curb doubts and suspicion from the Malays and foreign labourers against the British administration. The health institution doubled as an institution to the influence of nationalism consciousness which began to flourished amongst the educated Malay of the Middle East and foreign labourers in estates and mines to oppose British colonization. Throughout the British administration until the 1930s, expenditures and financing of the cost of medical treatment and provision of rural health facilities were halted and limited to finance British expenses exclusively in Perak and this situation remained until the end of the first phase of the British administration in Perak.